Vibration elicited vasoconstrictor reflex in Raynaud's phenomena. Issue 6 (June 1988) - Olsen, N; Petring, O U
Abstract : The fingers of seven women with primary Raynaud's phenomenon (PRP), 10 female controls, seven men with vibration induced white finger (VWF), and eight male controls were exposed to vibration and the relative change in finger capillary blood flow was measured by an atraumatic 133xenon washout technique without and during proximal nervous blockade. All four groups showed a vasoconstriction to vibration (p less than or equal to 0.02) which was abolished by proximal nervous blockade. Women with PRP had an augmented response to vibration (p less than 0.01) and men with VWF had a normal response (p greater than 0.10) when compared with that of their respective sex matched controls. The results show the existence of a vibration elicited central sympathetic vasoconstrictor reflex in the normal finger and in fingers affected by PRP and VWF. The results indicate a hyperreactivity of the central sympathetic nervous system in PRP and VWF and a dysfunction of the peripheral sensory nerve fibres in subjects with VWF. The described vibration test may be of guidance in the differentiation of PRP from VWF.